Features and prospects of innovative development of retail trade in modern conditions - O. Godina; L. Maksimenko; E. Tatasheva; M. Tochiev (Вестник Северо-Кавказского федерального университета)
The article deals with the issues of innovative development of the retail business in a new paradigm of perception of the world, in which technologies develop faster than one generation is replaced by another. Since the basis of innovations in retail are achievements in the field of artificial intelligence, which allow optimizing costs, organizing storage and transportation of goods, attracting buyers, etc., when creating new formats of relationships with consumers, it is important to proceed from the degree of readiness of both target segments and merchants themselves to engage in a unique consumer experience. The analysis of the degree of readiness of the regional retail business for new initiatives made it possible to prioritize the areas of constant changes in their trading activities, taking into account the growth of sustainable trends in industry development. In this connection, it is argued that it is important to learn how to model your behavior through the practice of experimentation, to balance your business models, ensuring the flexibility of all processes and thinking.